Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd010856
|View full text |Cite
|
Sign up to set email alerts
|

Water fluoridation for the prevention of dental caries

Abstract: Water fluoridation for the prevention of dental caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
178
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(189 citation statements)
references
References 17 publications
4
178
1
6
Order By: Relevance
“…A more recent review did not identify evidence that satisfied its inclusion criteria in determining the effectiveness of water fluoridation for adults. 4 However, that review was criticized for adopting unrealistic and inappropriate inclusion criteria. 5 Australian research on the benefit of fluoridation for adult caries experience initially focussed on young or middle-aged adults in the armed services.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent review did not identify evidence that satisfied its inclusion criteria in determining the effectiveness of water fluoridation for adults. 4 However, that review was criticized for adopting unrealistic and inappropriate inclusion criteria. 5 Australian research on the benefit of fluoridation for adult caries experience initially focussed on young or middle-aged adults in the armed services.…”
Section: Introductionmentioning
confidence: 99%
“…This debate has been the focus of three international committees, and was the reason for commissioning them. It also instigated the Cochrane's systematic review (Iheozor-Ejiofor et al 2015). Perhaps the major difference between the Israeli experts who oppose fluoridation, such as the Adin Committee experts or the Water Authority experts and their counterparts abroad is the unwillingness of the Israeli experts to voice their reservations in the media.…”
Section: 2mentioning
confidence: 99%
“…The authors of this review concluded that there is very little updated and high-quality evidence indicating that fluoridation reduces dental caries, while there is significant association between fluoride levels and dental fluorosis (Iheozor-Ejiofor et al 2015).…”
mentioning
confidence: 99%
“…2 A recent Cochrane systematic review on CWF and dental caries concluded that the availability of contemporary evidence is scarce, with most studies conducted prior to 1975. 3 Further, evidence on the effect of CWF cessation on dental caries is especially limited. 4 Cessation of CWF appears to be increasing in frequency in some regions.…”
Section: Introductionmentioning
confidence: 99%